THE PERCEPTION OF ISLAMIC RELIGIOUS EDUCATION AND ITS IMPLICATIONS FOR CURRICULUM DEVELOPMENT IN THE ERA OF SOCIETY 5.0 - Md Sawari, Siti Salwa; Muflihin, Ahmad; Warsiyah, Warsiyah; Madrah, Muna Yastuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
Based on the Digital Civility Index (DCI), Indonesian internet users are ranked at the lowest position within Southeast Asia in terms of their Digital Civility Index. This observable trend is closely associated with the proliferation of fake information, hate speech, cyberbullying, discriminatory behavior, and instances of fraud. Additionally, the process of modernization has significantly increased the consumptive tendencies within people's lifestyles. It is essential to note that Indonesia, with the world's largest Muslim population, is deeply rooted in religious beliefs. The country is ready to face the coming era of what is known as the era of society 5.0. Therefore, this study analyzed the public perception among urban dwellers in Semarang, focusing on the role of religious education as an aspect of curriculum development in the era of Society 5.0. In this context, the qualitative analysis was conducted using a method of phenomenology to obtain data through interviews, observations, and documentation. The results showed that contextualization of the Islamic religious education curriculum was needed to suit the needs of society. Islamic religious education taught students the physical (shari'a) and the spiritual dimensions (essential) to improve spirituality for urban Muslim communities as a basis for values in everyday behavior. In this context, the education instilled the importance of monotheism and ethics in using technology. Even though the era of Society 5.0 placed humans at the center (anthropocentric), the concept of Islamic religious education instilled the notion of God remaining at the centre (theocentric).